How structured yeast multicellular communities live, age and die? - Váchová, Libuše; Palková, Zdena (FEMS yeast research, 2018)
Yeasts, like other microorganisms, create numerous types of multicellular communities, which differ in their complexity, cell differentiation and in the occupation of different niches. Some of the communities, such as colonies and some types of biofilms, develop by division and subsequent differentiation of cells growing on semisolid or solid surfaces to which they are attached or which they can penetrate. Aggregation of individual cells is important for formation of other community types, such as multicellular flocs, which sediment to the bottom or float to the surface of liquid cultures forming flor biofilms, organized at the border between liquid and air under specific circumstances. These examples together with the existence of more obscure communities, such as stalks, demonstrate that multicellularity is widespread in yeast. Despite this fact, identification of mechanisms and regulations involved in complex multicellular behavior still remains one of the challenges of microbiology. Here, we briefly discuss metabolic differences between particular yeast communities as well as the presence and functions of various differentiated cells and provide examples of the ability of these cells to develop different ways to cope with stress during community development and aging.
Keywords: Microbiota; mikrobiální interakce; Candida; Saccharomyces; mikrobiální viabilita; mikrobiota; Microbial Viability; Microbial Interactions